The Prevalence Rate Of Anisometropia Among Students Of FKIK Ukrida Class 2023 - Ramadhan, Dafa Zahara; FarFar, Inggrid Osya (Jurnal MedScientiae, 2025)
Anisometropia is a different refractive power between the two eyes. Anisometropia can cause various symptoms, such as eye fatigue, headaches, blurred vision, diplopia (double vision), and decreased depth of vision (stereopsis). This will definitely interfere with learning activities, especially in college students. Purpose: This study aims to determine the prevalence and characteristics of anisometropia in university students. Methods: This study used total sampling technique with cross sectional method with 150 patients as respondents. Data collection time in this study was conducted from August 2023 to September 2023. Results: In this study as many as 66.7% (100 people) experienced anisometropia. A total of 12.7% (19 people) experienced simple myopic anisometropia, as many as 2% (3 people) experienced simple hypermetropic anisometropia, as many as 8% (12 people) experienced simple myopic astigmatism, as many as 12% (18 people) experienced compound myopic anisometropia, as many as 31.3% (47 people) experienced compound myopic astigmatism anisometropia, as many as 7% (1 person) experienced mixed anisometropia. Conclusion: The prevalence of anisometropia in this study was 66.7% (100 people). The most common type of anisometropia in this study is compound myopic astigmatism. From this study, it is hoped that it can increase public awareness to carry out sharp vision checks early on, so that learning activities can be more effective.